Lipid profile in Bangladeshi patients with type-2 diabetes: a series of 101 cases - Aktar Siddiqui, Syeda Rumman; Zillur Rahman, Mohammad (International Journal Of Community Medicine And Public Health, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a major public health concern in Bangladesh, affecting over 13 million people, with prevalence rising due to urbanization, sedentary lifestyles, and demographic changes. Dysfasting lipidemia, characterized by abnormal fasting lipid profiles, substantially increases cardiovascular disease (CVD) risk in T2DM patients. This study aimed to assess the fasting lipid profile among Bangladeshi type 2 medicated diabetic patients. Methods: This cross-sectional descriptive study was conducted at the Department of Laboratory Medicine, Epic Health Care Limited, Chattogram, Bangladesh, from December 2023 to May 2024. A total of 101 medicated T2DM patients were enrolled. Data were analyzed using SPSS Version 23.0. Results: The most frequent age group was 45–54 years (30.7%), with a mean age of 50.11±11.87 years. Females constituted 60.6% of participants. Desirable total cholesterol (<200 mg/dl) was observed in 59.4% of patients, while 20.8% had borderline and 19.8% high levels (mean: 193.00±51.07 mg/dl). Low high-density lipoprotein (HDL) (<40 mg/dl) was highly prevalent (73.3%), with a mean of 37.21±8.64 mg/dl. Optimal low-density lipoprotein (LDL) (<99 mg/dl) was noted in 45.5% (mean: 108.18±30.53 mg/dl). Triglycerides were normal in 33.7%, borderline in 24.8%, high in 35.5%, and very high in 5.9%, with a mean of 221.67±154.80 mg/dl. Conclusions: Despite mostly desirable cholesterol levels, the high prevalence of low HDL and elevated triglycerides indicates a considerable dyslipidemic burden, necessitating targeted lipid management to reduce CVD risk among Bangladeshi T2DM patients.